Professor Jacek Łuczak (1934-2019) – the palliative care pioneer - Bogusz, Halina (Medycyna Paliatywna/Palliative Medicine, 2020)
Professor Jacek Łuczak MD, PhD, FRCP, physician, specialist in internal medicine, cardiology, and palliative medicine. He devoted more than half of his sixty-year medical career to incurably ill, dying cancer patients. He was one of the most important leaders of the Polish hospice movement, and he organised first palliative care academic department in Central Europe. He was the co-founder and the first Head of the National Council for Palliative and Hospice Care (1993). He was one of the authors of National Palliative Care Development Program (1998). In 1999 together with other leaders, he created the Eastern and Central European Palliative Task Force (ECEPT). His charismatic leadership was based on the ability to build a deep relationship with each patient, volunteer, and student. He engaged in many activities, both organisational and educational. He was also active in the research and promotion of effective therapies. His Hospice Palium became a teaching centre and a model for Poland, and Central and Eastern Europe.